Observation of magnetic resonance and Faraday rotation in a spinel ZnCr2Se4 single crystal in the terahertz region. (23rd September 2016) - Zhang, Peng; Su, Fuhai; Chen, Xuliang; Zhang, Shile; Mei, Hongying; Yang, Zhaorong; Dai, Jianming; Pi, Li
Abstract: The terahertz (THz) time domain spectroscopy (THz-TDS) of a ZnCr2 Se4 single crystal has been performed under magnetic fields up to 9 Tesla at low temperatures. It was found that the magnetic resonance absorption originating from screw-spin-structure precession emerges in the THz region and evolves into ferromagnetic resonance absorption with the application of an external magnetic field. Benefiting from the phase- and polarization-sensitive detection technique of THz-TDS, the THz Faraday rotations of ZnCr2 Se4 were observed in both time and frequency domains, whose temperature and magnetic field dependences manifest typical magnetic structure transitions.